The Justiciability of Socio-Economic Rights in Indonesia: The Importance of Ratifying the Optional Protocol to the ICESCR - Erna Dyah Kusumawati (Faculty of Law, Universitas Padjadjaran, 2014)
AbstractThis article aims to analyse how the Indonesian government complies with obligations enshrined in the International Covenant on Economic, Social, and Cultural Rights (ICESCR). Furthermore, this study will assess how the national law provides justiciability as well as redress if the violations of socio-economic rights occur. The protection of socio-economic rights in Indonesia is enshrined in the Constitution, the Human Rights Law Act, and other thematic acts; such as the Children Protection Act, Labour Act, etc. However, some violations have occurred these days both by commission and omission of the government, such as in the Lapindo and Mesuji case. These two cases show that the rights to adequate housing, work, health, healthy environment, and rights to land have been severely violated. In the case of Lapindo, the decision of the court regarding the violations of socio-economic rights was unreasonable; they did not even put the element of tort into consideration for their decision concerning the human rights norm. For the second case, the process of legal settlement is still ongoing. Thus, the government has to establish a comprehensive policy to redress the violation of the socio-economic rights as these rights are not justiciable before the national law. If national law does not provide enforcing element, citizens will have no place to file a complaint for the violation of socio-economic rights. The Optional Protocol to the (OP to the ICESCR) provides individual communication to the Committee (CESCR). Reflecting from the cases of Lapindo and Mesuji, this paper will elaborate how the OP to the ICESCR guarantees the justiciability of socio-economic rights.Keywords: individual communication, justiciability, economic and social rights, state obligation, Committee CESCR. Justisiabilitas Hak-hak Ekonomi dan Sosial di Indonesia: Pentingnya Meratifikasi Protokol Tambahan Kovenan Internasional Hak-hak Ekonomi, Sosial, dan Budaya (KIHESB)AbstrakArtikel ini bertujuan untuk menganalisis kepatuhan pemerintah Indonesia terhadap kewajiban memenuhi hak ekonomi, sosial dan budaya (ekosob). Selain itu artikel ini akan menguji bagaimana hukum nasional menyediakan justisiabilitas termasuk ganti rugi jika pelanggaran terjadi. Perlindungan hak ekosob di Indonesia terdapat dalam berbagai hukum nasional, seperti Undang-undang Dasar Tahun 1945, Undang-undang Hak Asasi Manusia, serta undang-undang tematik lainnya (Undang-Undang Perlindungan Anak, Perburuhan dan lain-lain). Meskipun demikian pelanggaran hak bidang ekosob masih sering terjadi baik secara sengaja maupun lalai, antara lain kasus lumpur Lapindo dan kasus Mesuji. Pemerintah harus mengeluarkan kebijakan yang bersifat komprehensif untuk penegakan hukum dalam hal terjadi pelanggaran hak ekosob, karena hak-hak ini tidak dapat diadili dalam hukum nasional. Jika hukum nasional memiliki unsur penegak hukum tersebut, maka warga negara tidak dapat mengajukan komplain atas pelanggaran. Protokol Tambahan atas Kovenan Internasional tentang Hak-hak Ekonomi, Sosial, dan Budaya (OP) menyediakan komunikasi individual kepada Komite Ekosob (CESCR). Berkaca dari kasus lumpur Lapindo dan Mesuji, maka artikel ini akan memperinci bagaimana Protokol Tambahan akan menjamin justisiabilitas hak ekosob warga negara.Kata Kunci: komunikasi individual, justisiabilitas, hak-hak ekonomi dan sosial, kewajiban negara, komite CESCR. DOI: https://doi.org/10.22304/pjih.v1n2.a8